Isolation of an atypically small lipoamide dehydrogenase involved in the glycine decarboxylase complex from Eubacterium acidaminophilum. - Freudenberg, W (1989)
The lipoamide dehydrogenase of the glycine decarboxylase complex was purified to homogeneity (8 U/mg) from cells of the anaerobe Eubacterium acidaminophilum that were grown on glycine. In cell extracts four radioactive protein fractions labeled with D-[2-14C]riboflavin could be detected after gel filtration, one of which coeluted with lipoamide dehydrogenase activity. The molecular mass of the native enzyme could be determined by several methods to be 68 kilodaltons, and an enzyme with a molecular mass of 34.5 kilodaltons was obtained by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Immunoblot analysis of cell extracts separated by sodium dodecyl sulfate-polyacrylamide or linear polyacrylamide gel electrophoresis resulted in a single fluorescent band. NADPH instead of NADH was the preferred electron donor of this lipoamide dehydrogenase. This was also indicated by Michaelis constants of 0.085 mM for NADPH and 1.1 mM for NADH at constant lipoamide and enzyme concentrations. The enzyme exhibited no thioredoxin reductase, glutathione reductase, or mercuric reductase activity. Immunological cross-reactions were obtained with cell extracts of Clostridium cylindrosporum, Clostridium sporogenes, Clostridium sticklandii, and bacterium W6, but not with extracts of other glycine- or purine-utilizing anaerobic or aerobic bacteria, for which the lipoamide dehydrogenase has already been characterized.